Efek Perbedaan Penggunaan Umpan Terhadap Hasil Tangkapan Pancing Ulur Di Desa Fidatan Pulau Ubur Kota Tual - Notanubun, Julianus; Thenu, Imanuel M.; Ngamel, Yuliana Anastasia; Tanarubun, Tuti (Fakultas Perikanan dan Ilmu Kelautan, Universitas Papua, 2023)
Hand line is a type of fishing gear that is active and environmentally friendly and is often used by traditional fishermen to catch fish with high economic value. The right bait is one of the factors for maximizing catches. Fishermen around the village of Fiditan, Jellyfish Island, Kota Tual generally use various kinds of bait, such as Momar fish (Decapterus sp), Sikuda fish (Letrinus lenca) and Nipah worms (Namalycastis). This research was held in November – December 2022. The objectives are: to know the composition of hand line catches with different baits and to determine the type of bait that gives the most catches. This research is expected to provide information and knowledge to fishermen about hand line fishing gear units using different baits. Data analysis used a randomized block design, with baits used were Momar fish, Sikuda fish and Nipah worms. During the study, a total of 346 fish were caught consisting of Sikuda fish (Letrinus lenca) with a total of 294 fish (85.5%), followed by Gora fish (Lutjanus carponotatus) 25 individuals (7.33%), Sand-sand fish ( Taeniura ymma) 20 individuals (1.16%) and the smallest catch was Gace fish (Lutjanus malabericus) with a total of 1 fish (0.29%). The results of the analysis of variance showed that the Fcount for the treatment (8.66) was greater than the Ftable (0.05); 14:2) (88.5) so statistically H0. This means that the difference in the use of bait has a very significant effect at the level of ά = 0.05 on the catch. The BNT test results also showed differences in the value of each bait so that it was concluded that the three baits used by fishermen had a significant difference in the catch obtained with Sikuda bait with the highest yield, followed by Nipah worm and Momar fish bait.